Knowledge hiding in teachers of moral education degree programs in Pakistan: The role of servant leadership, psychological ownership, and perceived coworker support - Anwaar, Saima; Jingwei, Liu (Frontiers in Psychology, 2022)
The purpose of this research is to examine the influence of servant leadership on teachers of moral education degree programs in Pakistan. By utilizing social learning, we propose that servant leadership and perceived coworker support can reduce the knowledge hiding by enhancing the sense of organization-based psychological ownership. The findings of time-lagged and multi-source data indicate that servant leadership has a negative relationship with knowledge hiding. Our results also indicate that psychological ownership mediates the effects of servant leadership on knowledge hiding. Moreover, a higher level of perceived coworker support enhances the sense of psychological ownership which helps to reduce knowledge hiding. This research extends strong support for the proposition that servant leaders who adopt an employee-centered management approach, stressing personal integrity and care for employees significantly affect employee attitudes and behaviors. Moreover, this study suggests that managers should demonstrate care toward their subordinates which helps them to reduce negative behaviors (e.g., knowledge hiding).